Geneva Statement on Heritable Human Genome Editing: The Need for Course Correction. Issue 4 (April 2020) - Andorno, Roberto; Baylis, Françoise; Darnovsky, Marcy; Dickenson, Donna; Haker, Hille; Hasson, Katie; Lowthorp, Leah; Annas, George J.; Bourgain, Catherine; Drabiak, Katherine; Graumann, Sigrid; Grüber, Katrin; et al.
Abstract : As public interest advocates, policy experts, bioethicists, and scientists, we call for a course correction in public discussions about heritable human genome editing. Clarifying misrepresentations, centering societal consequences and concerns, and fostering public empowerment will support robust, global public engagement and meaningful deliberation about altering the genes of future generations.